Factors Affecting Software Development Productivity: An empirical study - Canedo, Edna Dias; Santos, Giovanni Almeida (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
The competitiveness has demanded from the software industry shorter delivery times for its products resulting in optimized life cycles, generating a need to increase its performance to maintain competitiveness in the markets where they operate. This context has made productivity study so fundamental that organizations not only evaluate their performance, but also provide means to improve it. The main goal of this paper is to investigate which factors affect productivity in software development projects and in open-source projects. In this work a Systematic Literature Review (SLR) was carried out in order to answer the research questions and a survey with practitioners community about their perception in relation to the factors of the productivity of the team. This empirical study led to the discovery of interesting factors that show how the different factors do (or do not) affect productivity. It was also found out that some factors appear to allow independence and responsibility of team, while others appear to cause a better distribution of tasks. The results show how factors such as people, product, organization, investment in technology, lack of contractual relations and engagement of open-source project contributors influence productivity.